Numerical investigation on ultra-high performance concrete beam under pure bending. (December 2021) - Kumar, S. Charles Ruskin; Anuradha, R.; Dharmaraj, R.
Abstract: Ultra high performance concrete applications are increasing, widely on all state of construction due to its reliability over its strength and convenience. With this concern, many studies started to experimentally explore the properties of ultra-high performance concrete at various concerns. All these studies are focused on increasing the performance of this contemporary concrete through optimization of resources and additive materials. In the row, this study considers the performance of the concrete through the spacing of shear connectors (100 mm and 150 mm). However, in addition, the optimum percentage of inclusion and length of steel fibres directing with different proportions of (1%, 2%, of 6 mm, 1%, 2% of 13 mm, 1% of 6 mm and 1% of 13 mm, 1% of 6 mm and 2% of 13 mm). This investigation involves two phases namely experimental and numerical, in which the experimental results are directed as inputs to numerical analysis. From the findings, it can be concluded the optimum spacing of shear connector with length and percentage of inclusion of steel fibres reinforcement. Results conclude that 2% of 13 mm steel fibre with 150 mm spacing of shear connector provides better results compared to other concerned combinations under pure bending with the considerations of flexural and bending behavior. With these results, this study provides both scientific and technical contributions also further this study enlighten the future enhancements in the concerned field of applications. Highlights: Examined the basic behavioral properties of UHPC beams with steel rebar under pure bending. Different spacing of stirrups along with varying percentages proportion of inclusion of steel fibres has been considered. Bending behavior of different combination ​was investigated with experimental phase and numerical phase. Experimental results are redirected to numerical phase to establish the bending behavior of UHPC beams under pure bending.